"Nobody's Mule": Black Womanist Caring-Agency, Urban Charters, and the Choice to (Not) Teach. Issue 3 (3rd July 2021) - Benson, Tracey A.; Salas, Spencer; Dolet, Tia; Jones, Bianca
ABSTRACT: Urban charter schools targeting Black communities struggle to recruit Black teachers and even more to retain them. At the same time that scholarship has begun to recenter Black and Brown teachers' lives, the narrated perspectives of Black women teachers are often drowned out in urban educational reform's Hollywoodization. In this article, we story Nina Sinclair's 7-year teaching trajectory across five urban charters in two states to examine her layered Black womanist caring-agency. As our analysis demonstrates, for Sinclair, it was not enough just to teach. She wanted the autonomy to create motivating and engaging instruction to inspire her students and herself to do and be more. She wanted to be in a place where she could grow professionally; where she would be mentored, supported, and challenged; and where she could enjoy being Nina Sinclair with like-minded people. All of these things mattered because she mattered. Organizing Sinclair's pivots in and out of the charter school classroom through a quare framework, we theorize her shifting professional movements for being whole. Our findings frame Sinclair's self-care—her freedom to choose what she wanted to do, to be, to stop, to slow down, to picture what if and what else—as the legacy her ancestors had bequeathed her and as an underexamined but no less important dimension of her agentive caring.